A Review of Bamboo: Characteristics, Components, and Its Applications - Budi Irawan; Muhammad Ihsan; Muhamad Diki Permana; Atiek Rostika Noviyanti (Journal of Natural Fibers)
The utilization of tropical lignocellulosic biomass is gaining momentum in renewable energy and sustainable material applications. This review focuses on bamboo, a fast-growing resource with high cellulose content and strong mechanical properties. A systematic analysis of Scopus-indexed publications (1990–2024) highlights bamboo’s potential in bioenergy, biocomposites, and environmental remediation. Beyond its industrial value, bamboo holds cultural and economic significance for Indigenous and local communities, traditionally used in construction, tools, crafts, and music. These practices reflect deep ecological knowledge. Despite its promise, bamboo remains underrepresented in biomass research compared to temperate species, revealing a knowledge gap. Research is dominated by environmental science, aligning with global sustainability goals. However, challenges such as lignin removal efficiency and species-specific variability persist, hindering large-scale bioenergy applications. For instance, high hemicellulose content in species like Gigantochloa apus may offer advantages in fermentation efficiency. This review emphasizes the importance of selecting suitable biomass species and tailoring conversion technologies based on chemical composition. By integrating technical insight with socio-ecological context, this work supports the sustainable and culturally informed development of tropical biomass resources – especially bamboo – for future industrial and environmental applications.